Bacteriophage‐induced aggregation of oil sands tailings1. Issue 3 (1st November 2012) - Curtis, Susan B.; Dunbar, W. Scott; MacGillivray, Ross T.A.
Abstract Very large quantities of tailings are produced as a result of processing oil sands. After the sand particles settle out, a dense stable mixture of clay, silt, water with residual bitumen, salts, and organics called mature fine tailings (MFT) can remain in suspension for decades. Research into developing methods that would allow consolidation and sedimentation of the suspended particles is ongoing. We have studied the ability of a filamentous bacteriophage (called VP12 bearing the peptide DSQKTNPS at the N‐terminus of the major coat protein pVIII) to aggregate MFT. To understand the biophysical basis of the aggregation, phage‐induced aggregation of diluted MFT was measured at room temperature under varying conditions of pH, salt, detergent. Phage at concentrations of 5.0 × 1011/mL to 1012/mL induced rapid settling of the diluted MFT. The addition of sodium chloride (10 mM) lowered the concentration of phage required to induce aggregation. Since the non‐ionic detergents Triton‐X 100 and Tween‐20, and the ionic detergent sodium deoxycholate had little effect, hydrophobic interactions do not appear to be a major contributor to the phage‐induced aggregation of MFT. However, aggregation was prevented at pH values higher than 9.0 suggesting that positively charged amino acid residues are required for MFT aggregation by phage. Genetic engineering of the pVIII peptide sequence indicated that hydrogen bonding also contributes to phage‐induced aggregation. In addition, replacing the basic residue lysine with an alanine in the recombinant peptide of VP12 completely prevented phage‐induced aggregation. Three other phage displaying different amino acid sequences but all containing a lysine in the same position had variable aggregation efficiencies, ranging from no aggregation to rapid aggregation. We conclude that not only are the functional groups of the amino acids important, but the conformation that is adopted by the variable pVIII peptide is also important for phage‐induced MFT aggregation. Biotechnol. Bioeng. 2013; 110: 803–811. © 2012 Wiley Periodicals, Inc.